PENGEMBANGAN MEDIA INTERAKTIF TERINTEGRASI NILAI KEISLAMAN BERBANTUAN SOFTWARE MACROMEDIA FLASH 8 PADA MATERI LINGKARAN - Salsabila, Yumna Lulu; Bambang Sri Anggoro; Siska Andriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an interactive learning medium assisted by Macromedia Flash 8 software, integrated with Islamic values, on the topic of circles for eight-grade junior high school students. The background of this research is based on the low interest and understanding of students in learning mathematics, particularly in the topic of circles. In addition, the learning media used by teachers are still less varied, and there is no interactive mathematics learning medium integrated with Islamic values, which makes the learning process less engaging. The research method employed is Research and Development (R&D) using the ADDIE model, which consists of five stages analysis, design, development, implementation, and evaluation. The research instruments include validation questionnaires, student response questionnaires, and learning outcome tests. The validation results show that the material expert obtained a score of 3.74 (feasible), the media expert obtained 3.76 (feasible), and the Islamic studies expert obtained 3.50 (feasible). Student responses in the small group trial reached 3.29 and in the large group trial 3.39, both categorized as very interesting. Based on the calculation of the effect size of 0.56, the interactive learning medium is considered quite effective in improving students understanding of the concept of circles.